Preparation method and application of alginate-based carbon aerogel-loaded cobalt-lead carbonate composite material
By doping cobalt into the lead-based electrocatalyst and preparing carbon aerogel-supported composite materials using alginate, the problem of unstable valence state of the lead-based electrocatalyst during the carbon dioxide reduction process is solved, and the efficient and stable carbon dioxide reduction effect is achieved.
Patent Information
- Application Number
- CN202211644283.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-12-20
AI Technical Summary
The existing lead-based electrocatalysts are easily oxidized in the carbon dioxide saturated electrolyte and are easily reduced during the carbon dioxide reduction stage, resulting in unstable valence state and hindering the reduction of carbon dioxide to formic acid.
The preparation method of carbon aerogel-supported cobalt-lead carbonate composite based on alginate is adopted to adjust the external electronic structure of Pb2+ by doping cobalt lead to improve the stability and activity of the catalyst.
The efficient reduction of carbon dioxide to formic acid is achieved, with excellent selectivity and stability, and the Faraday efficiency of formic acid production of 98.15% at -0.7V vs. RHE voltage is achieved.
Smart Images

Figure CN115807234B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a carbon aerogel composite material. Background Art
[0002] Although the use of fossil energy has brought great convenience to mankind, it also causes a sharp rise in the concentration of carbon dioxide (CO2) in the atmosphere, leading to climate change and severe environmental problems. Converting CO2 into valuable high-value chemicals or fuels can alleviate the environmental problems caused by CO2 emissions and supplement energy. Electrocatalytic CO2 reduction reaction (CO2RR) technology has the characteristics of simple operation and mild conditions, and is currently a very promising technical means to achieve artificial carbon cycle.
[0003] Formic acid is an important industrial raw material used in the fields of chemical industry, energy, medicine, etc. For example, it can be used as an industrial reaction intermediate, fuel cell raw material, hydrogen storage medium, etc. As an important liquid product of electrocatalytic CO2RR, it has a small number of electrons transferred during the reaction (2 electrons) and a simple reaction path. It is one of the most economically viable products of CO2RR technology in commercial terms. Electrocatalyst materials play a key role in electrocatalytic CO2RR. In recent years, researchers have been committed to exploring new electrocatalysts for efficiently converting CO2 into formic acid. However, the intrinsic molecular inertness of CO2 affects the activity of the CO2RR reaction, and the diversity of products and competitive hydrogen evolution reaction (HER) reduce the selectivity for formic acid. These factors hinder the practical application of electrocatalytic CO2 conversion to formic acid. Lead-based electrocatalyst materials are considered to be promising CO2RR formic acid electrocatalysts because of their high H2 overpotential and easy adsorption of HCOO* intermediates. However, it is easily oxidized in carbon dioxide saturated electrolytes and easily reduced in the carbon dioxide reduction stage, resulting in valence instability. According to the latest research, Pb in lead-based electrocatalysts 2+ It is the actual active site, but ionic lead is often not conducive to activating *CO2 because of the loss of its outermost electrons, thus hindering the conversion of *CO2 to HCOO*, which in turn hinders the reduction of carbon dioxide to formic acid. Therefore, it is necessary to develop a method that can regulate Pb 2+ Electrocatalysts with electron-depleted environments are used to compensate for the outer electron-depleted environment structure to activate *CO2 and promote the generation of HCOO*. This is very necessary for efficiently converting CO2 into formic acid products for industrial applications. It also has important research significance and application prospects for alleviating the environmental crisis caused by CO2 and meeting the growing demand for chemicals. Summary of the invention
[0004] The purpose of the present invention is to solve the problem that the lead-based electrocatalyst material prepared by the existing method is easily oxidized in a carbon dioxide saturated electrolyte and easily reduced in the carbon dioxide reduction stage, resulting in unstable valence state, which hinders the reduction of carbon dioxide to formic acid, and to provide a method for preparing a carbon aerogel-loaded cobalt-lead carbonate composite material based on alginate.
[0005] The present invention aims at the deficiencies of existing research. The present invention uses sodium alginate, which is rich in sources, as the carbon substrate raw material, utilizes the mutual influence of the rich electronic environment between the bimetallic materials, and adopts cobalt doping lead to adjust Pb 2+ The external electronic structure of Pb 2+ The carbon aerogel catalyst with high carbon dioxide reduction electrocatalytic activity is prepared by obtaining electrons to alleviate the electron loss of the outermost layer, solving the problems of poor selectivity, poor stability, serious insufficient generation rate and poor performance of lead-based electrocatalysts in existing carbon dioxide reduction catalysts. The preparation process of the present invention is simple, no expensive equipment is required, the obtained product has excellent performance and good electrochemical stability, and has broad prospects in the promotion and application of carbon dioxide reduction;
[0006] A method for preparing a carbon aerogel-loaded cobalt-lead carbonate composite material based on alginate is specifically completed by the following steps:
[0007] 1. Preparation of sodium alginate-based cobalt-lead hydrogel:
[0008] ① Dissolve sodium alginate in deionized water and stir thoroughly to obtain sodium alginate hydrogel;
[0009] ②、Configuration containing Co 2+ With Pb 2+ The salt solution is stirred evenly to obtain a cobalt-lead salt ion solution;
[0010] ③, adding sodium alginate hydrogel dropwise into the cobalt-lead salt ion solution, stirring evenly, taking out after soaking for a certain period of time, washing, and obtaining sodium alginate-based cobalt-lead hydrogel;
[0011] 2. Preparation of aerogel:
[0012] The sodium alginate-based cobalt-lead hydrogel is frozen by liquid nitrogen and then placed in a freeze dryer for freeze drying to obtain the sodium alginate cobalt-lead aerogel;
[0013] 3. Carbonization:
[0014] The cobalt-lead aerogel of sodium alginate is placed in a tubular furnace for carbonization, then soaked and pickled with an acetic acid solution, taken out and washed with water to obtain a carbon aerogel composite material of cobalt-doped lead oxide loaded with sodium alginate; the carbon aerogel composite material of cobalt-doped lead oxide loaded with sodium alginate is immersed in a 0.1 mol / L KHCO3 electrolyte saturated with carbon dioxide to obtain a carbon aerogel-loaded cobalt-lead carbonate composite material based on alginate.
[0015] An alginate-based carbon aerogel-supported cobalt-lead carbonate composite was used as a CO2RR catalyst.
[0016] Principle of the present invention:
[0017] First, the bimetallic structure has abundant interactions between electrons. The doping of cobalt has an optimizing and regulating effect on the electronic structure of the lead carbonate catalytic site. The catalytic site affected by this regulation tends to have a more efficient catalytic ability. Therefore, the present invention uses the introduction of cobalt to induce lead carbonate to improve the CO2RR performance, which provides ideas for constructing bimetallic carbon dioxide reduction electrocatalysts and preparing low-cost non-precious metal carbon dioxide reduction electrocatalysts, and has important reference significance for the design of bimetallic synergistic electrocatalysts for carbon dioxide reduction.
[0018] 2. Sodium alginate is a natural linear polymer polysaccharide with a large number of -COO groups on its molecular chain. -COO can chelate with divalent metal ions to form an egg-box structure, thereby making alginate produce gel properties. Alginate containing different metal ions can be prepared by ion exchange. Cobalt ions and lead ions can be mixed with sodium alginate to obtain seaweed-based cobalt-lead hydrogel; after freeze-drying, sodium alginate-based cobalt-lead aerogel was obtained, and after carbonization, cobalt-doped lead oxide-loaded carbon aerogel composite materials of sodium alginate can be obtained; the alginate-based carbon aerogel-loaded cobalt-lead carbonate composite materials are obtained by further immersion with the physicochemical properties of lead itself; the lead loading is 73.82wt%, and the cobalt doping amount is only 13.18wt%, which can achieve high catalytic activity of CO2RR performance.
[0019] Advantages of the present invention:
[0020] 1. At present, carbon dioxide pollution is becoming increasingly serious, and formic acid is in great demand in all walks of life. Therefore, it is of great significance to develop a cheap and high-performance CO2RR catalyst to reduce carbon dioxide to formic acid. The preparation method of the present invention is simple. The raw material is marine polysaccharide-sodium alginate. Sodium alginate is extracted from brown algae, which has a wide source, is green and environmentally friendly, and has high safety. Cobalt and lead are non-precious metals with low prices, and the amount of doped Co is very low, which is only 17.8% of that of lead.
[0021] 2. The alginate-based carbon aerogel-loaded cobalt-lead carbonate composite material prepared by the method of the present invention has a very high CO2RR performance by doping a small amount of non-precious metal Co. It achieves a maximum Faraday efficiency of 98.15% formic acid production at a voltage of -0.7 V (vs. RHE), embodies excellent formic acid pathway selectivity and exhibits excellent catalytic stability;
[0022] 3. The alginate-based carbon aerogel-loaded cobalt-lead carbonate composite material prepared by the method of the present invention has a simple operation process, high yield, can be synthesized in large quantities, does not require expensive equipment, and the prepared material has good performance, low cost, simple synthesis, stable use, is suitable for promotion, and has broad prospects;
[0023] 4. The alginate-based carbon aerogel-loaded cobalt-lead carbonate composite material prepared by the present invention has excellent selectivity for reducing carbon dioxide to formic acid, and achieves a Faradaic efficiency of 98.15% formic acid production under a voltage condition of -0.7 V vs. RHE. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a scanning electron microscope image of the alginate-based carbon aerogel-loaded cobalt-lead carbonate composite material prepared in Example 1;
[0025] Figure 2 is a transmission electron micrograph of the alginate-based carbon aerogel-loaded cobalt-lead carbonate composite material prepared in Example 1;
[0026] Figure 3 is a high-resolution transmission electron microscopy image of the alginate-based carbon aerogel-loaded cobalt-lead carbonate composite material prepared in Example 1;
[0027] Figure 4 It is a linear scanning curve of the alginate-based carbon aerogel-loaded cobalt-lead carbonate composite material prepared in Example 1 under CO2 saturation and N2 saturation conditions measured by an electrochemical workstation and an H-type electrolytic cell;
[0028] Figure 5 is the Faraday efficiency of the product of the alginate-based carbon aerogel-supported cobalt-lead carbonate composite material prepared in Example 1 at a voltage of -0.6 V vs. RHE to -1.2 V vs. RHE, in which 1 is hydrogen, 2 is carbon monoxide, and 3 is formic acid;
[0029] Figure 6 The stability of the catalyst of the alginate-based carbon aerogel-supported cobalt-lead carbonate composite material prepared in Example 1 at a voltage of -0.7 V vs. RHE for 12 h;
[0030] Figure 7It is a linear scanning curve of the lead carbonate-loaded sodium alginate carbon aerogel composite material prepared in Comparative Example 1 under CO2 saturation and N2 saturation conditions measured by an electrochemical workstation and an H-type electrolytic cell;
[0031] Figure 8 It is the Faraday efficiency of the product of the lead carbonate-loaded sodium alginate carbon aerogel composite material prepared in Comparative Example 1 at a voltage of -0.6 V vs. RHE to -1.2 V vs. RHE, in which 1 is hydrogen, 2 is carbon monoxide, and 3 is formic acid;
[0032] Fig. 9 The stability of the catalyst of the lead carbonate-loaded sodium alginate carbon aerogel composite prepared in Comparative Example 1 at a voltage of -0.7 V vs. RHE for 10 h;
[0033] Fig.10 It is a linear scanning curve of the carbon aerogel composite material of cobalt-doped sodium alginate prepared in Comparative Example 2 under CO2 saturation and N2 saturation conditions measured by an electrochemical workstation and an H-type electrolytic cell;
[0034] Fig.11 It is the Faraday efficiency of the product of the cobalt-doped sodium alginate carbon aerogel composite material prepared in Comparative Example 2 at a voltage of -0.6 V vs. RHE to -1.2 V vs. RHE, in which 1 is hydrogen, 2 is carbon monoxide, and 3 is formic acid;
[0035] Fig.12 The stability of the catalyst of the cobalt-doped sodium alginate carbon aerogel composite material prepared in Comparative Example 2 at a voltage of -1.2 V vs. RHE for 10 h. DETAILED DESCRIPTION
[0036] The present invention is described below by way of specific embodiments, but is not intended to limit the present invention.
[0037] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention.
[0038] Specific implementation method 1: This implementation method is a method for preparing a carbon aerogel-loaded cobalt-lead carbonate composite material based on alginate, which is specifically completed according to the following steps:
[0039] 1. Preparation of sodium alginate-based cobalt-lead hydrogel:
[0040] ① Dissolve sodium alginate in deionized water and stir thoroughly to obtain sodium alginate hydrogel;
[0041] ②、Configuration containing Co 2+With Pb 2+ The salt solution is stirred evenly to obtain a cobalt-lead salt ion solution;
[0042] ③, adding sodium alginate hydrogel dropwise into the cobalt-lead salt ion solution, stirring evenly, taking out after soaking for a certain period of time, washing, and obtaining sodium alginate-based cobalt-lead hydrogel;
[0043] 2. Preparation of aerogel:
[0044] The sodium alginate-based cobalt-lead hydrogel is frozen by liquid nitrogen and then placed in a freeze dryer for freeze drying to obtain the sodium alginate cobalt-lead aerogel;
[0045] 3. Carbonization:
[0046] The cobalt-lead aerogel of sodium alginate is placed in a tubular furnace for carbonization, then soaked and pickled with an acetic acid solution, taken out and washed with water to obtain a carbon aerogel composite material of cobalt-doped lead oxide loaded with sodium alginate; the carbon aerogel composite material of cobalt-doped lead oxide loaded with sodium alginate is immersed in a 0.1 mol / L KHCO3 electrolyte saturated with carbon dioxide to obtain a carbon aerogel-loaded cobalt-lead carbonate composite material based on alginate.
[0047] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the mass fraction of sodium alginate in the sodium alginate hydrogel described in step 1① is 1%; the stirring in step 1① is sufficient stirring until there are no bubbles. The other steps are the same as those in specific implementation method 1.
[0048] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that: the cobalt-lead salt ion solution in step 1② contains Co 2+ The concentration of Pb is 0.1 mol / L. 2+ The concentration of is 0.2 mol / L. The other steps are the same as those in the first or second embodiment.
[0049] Specific implementation method 4: This implementation method is different from specific implementation methods 1 to 3 in that the soaking time in step 1 ③ is 5 hours. The other steps are the same as those in specific implementation methods 1 to 3.
[0050] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the washing in step 1 (3) is to use deionized water to wash until the filtered water is transparent and colorless. The other steps are the same as those of specific embodiments 1 to 4.
[0051] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that the freeze drying temperature in step 2 is -80°C and the freeze drying time is 24 hours. The other steps are the same as those in specific embodiments 1 to 5.
[0052] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the concentration of the acetic acid solution in step 3 is 1 mol / L and the immersion pickling time in the acetic acid solution in step 3 is 5 hours. The other steps are the same as those in specific embodiments 1 to 6.
[0053] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the carbonization atmosphere in step 3 is argon, and the carbonization process is: heating from room temperature to 700°C at a heating rate of 2°C / min, and then carbonizing at 700°C for 2.0h. The other steps are the same as those of specific embodiments 1 to 7.
[0054] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: after taking out in step 3, it is washed with water until pH = 7.0, which is neutral; in step 3, the cobalt-doped lead oxide-loaded sodium alginate carbon aerogel composite material is immersed in a 0.1 mol / L KHCO3 electrolyte saturated with carbon dioxide for 0.5 h. The other steps are the same as those of specific embodiments 1 to 8.
[0055] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that a carbon aerogel supported cobalt-lead carbonate composite material based on alginate is used as a CO2RR catalyst. The other steps are the same as those of specific embodiments 1 to 9.
[0056] The following examples are used to verify the beneficial effects of the present invention:
[0057] Example 1: A method for preparing a carbon aerogel-loaded cobalt-lead carbonate composite material (Co-PbCO3@CNS) based on alginate, which is specifically completed by the following steps:
[0058] 1. Preparation of sodium alginate-based cobalt-lead hydrogel:
[0059] ① Dissolve sodium alginate in deionized water and stir thoroughly to obtain sodium alginate hydrogel;
[0060] The mass fraction of sodium alginate in the sodium alginate hydrogel described in step 1① is 1%;
[0061] In step 1①, stir thoroughly until there are no bubbles;
[0062] ②, dissolve cobalt nitrate hexahydrate and lead nitrate in deionized water, stir evenly, and obtain a cobalt-lead salt ion solution;
[0063] The cobalt-lead salt ion solution in step 1② is 2+ The concentration of Pb is 0.1 mol / L. 2+ The concentration is 0.2 mol / L;
[0064] ③, adding sodium alginate hydrogel dropwise into the cobalt-lead salt ion solution, immersing for a certain period of time, taking it out, washing it, and obtaining sodium alginate-based cobalt-lead hydrogel;
[0065] The soaking time described in step 1③ is 5h;
[0066] The washing in step 1 (3) is to use deionized water to wash until the filtered water is transparent and colorless;
[0067] 2. Preparation of aerogel:
[0068] The sodium alginate-based cobalt-lead hydrogel is frozen by liquid nitrogen and then placed in a freeze dryer for freeze drying to obtain the sodium alginate cobalt-lead aerogel;
[0069] The freeze-drying temperature in step 2 is -80°C, and the freeze-drying time is 24 hours.
[0070] 3. Carbonization:
[0071] The cobalt-lead aerogel of sodium alginate was placed in a tubular furnace for carbonization, then soaked and pickled with an acetic acid solution, and then washed with water to obtain a cobalt-doped lead oxide-loaded sodium alginate carbon aerogel composite material; the cobalt-doped lead oxide-loaded sodium alginate carbon aerogel composite material was immersed in a 0.1 mol / L KHCO3 electrolyte saturated with carbon dioxide for 0.5 h to obtain an alginate-based carbon aerogel-loaded cobalt-lead carbonate composite material (Co-PbCO3@CNS);
[0072] The concentration of the acetic acid solution described in step 3 is 1 mol / L;
[0073] The acetic acid solution is used for pickling for 5 hours in step 3;
[0074] The carbonization atmosphere in step 3 is argon, and the carbonization process is: heating from room temperature to 700°C at a heating rate of 2°C / min, and then carbonizing at 700°C for 2.0h;
[0075] After being taken out in step 3, the mixture is washed with water until the pH value reaches 7.0, which is neutral.
[0076] Comparative Example 1: A method for preparing a lead carbonate-loaded sodium alginate carbon aerogel composite material (PbCO3@CNS), which is specifically completed by the following steps:
[0077] 1. Preparation of sodium alginate-based lead hydrogel:
[0078] ① Dissolve sodium alginate in deionized water and stir thoroughly to obtain sodium alginate hydrogel;
[0079] The mass fraction of sodium alginate in the sodium alginate hydrogel described in step 1① is 1%;
[0080] In step 1①, stir thoroughly until there are no bubbles;
[0081] ② Dissolve lead nitrate in deionized water and stir evenly to obtain a lead salt ion solution;
[0082] Pb in the lead salt ion solution described in step 1② 2+ The concentration is 0.1 mol / L;
[0083] ③, adding sodium alginate hydrogel dropwise into the lead salt ion solution, taking it out after soaking for a certain period of time, washing it, and obtaining sodium alginate-based lead hydrogel;
[0084] The soaking time described in step 1③ is 5h;
[0085] The washing in step 1 (3) is to use deionized water to wash until the filtered water is transparent and colorless;
[0086] 2. Preparation of aerogel:
[0087] The sodium alginate-based lead hydrogel is frozen by liquid nitrogen and then placed in a freeze dryer for freeze drying to obtain the sodium alginate-based lead aerogel;
[0088] The freeze drying temperature in step 2 is -80°C and the freeze drying time is 24h;
[0089] 3. Carbonization:
[0090] The lead aerogel of sodium alginate is placed in a tubular furnace for carbonization, then soaked and pickled with an acetic acid solution, and then washed with water to obtain a carbon aerogel composite material of lead oxide loaded with sodium alginate; the carbon aerogel composite material of lead oxide loaded with sodium alginate is soaked in a 0.1 mol / L KHCO3 electrolyte saturated with carbon dioxide for 0.5 h to obtain a carbon aerogel composite material of lead carbonate loaded with sodium alginate (PbCO3@CNS);
[0091] The concentration of the acetic acid solution described in step 3 is 1 mol / L;
[0092] The acetic acid solution is used for pickling for 5 hours in step 3;
[0093] The carbonization atmosphere in step 3 is argon, and the carbonization process is: heating from room temperature to 700°C at a heating rate of 2°C / min, and then carbonizing at 700°C for 2.0h;
[0094] After being taken out in step 3, the mixture is washed with water until the pH value reaches 7.0, which is neutral.
[0095] Comparative Example 2: A method for preparing a cobalt-doped sodium alginate carbon aerogel composite material (Co@CNS), which is specifically completed by the following steps:
[0096] 1. Preparation of sodium alginate-based cobalt hydrogel:
[0097] ① Dissolve sodium alginate in deionized water and stir thoroughly to obtain sodium alginate hydrogel;
[0098] The mass fraction of sodium alginate in the sodium alginate hydrogel described in step 1① is 1%;
[0099] In step 1①, stir thoroughly until there are no bubbles;
[0100] ② Dissolve cobalt nitrate hexahydrate in deionized water and stir evenly to obtain a cobalt salt ion solution;
[0101] The cobalt salt ion solution in step 1② is Co 2+ The concentration is 0.1 mol / L;
[0102] ③, adding sodium alginate hydrogel dropwise into the cobalt salt ion solution, taking it out after soaking for a certain period of time, washing it, and obtaining sodium alginate-based cobalt hydrogel;
[0103] The soaking time described in step 1③ is 5h;
[0104] The washing in step 1 (3) is to use deionized water to wash until the filtered water is transparent and colorless;
[0105] 2. Preparation of aerogel:
[0106] The sodium alginate-based cobalt hydrogel is frozen by liquid nitrogen and then placed in a freeze dryer for freeze drying to obtain the sodium alginate cobalt aerogel;
[0107] The freeze-drying temperature in step 2 is -80°C, and the freeze-drying time is 24 hours.
[0108] 3. Carbonization:
[0109] The sodium alginate cobalt aerogel is placed in a tubular furnace for carbonization, then soaked and pickled with an acetic acid solution, and then washed with water to obtain a cobalt-doped sodium alginate carbon aerogel composite material; the cobalt-doped sodium alginate carbon aerogel composite material is soaked in a 0.1 mol / L KHCO3 electrolyte saturated with carbon dioxide for 0.5 h to obtain a cobalt-doped sodium alginate carbon aerogel composite material (Co@CNS);
[0110] The concentration of the acetic acid solution described in step 3 is 1 mol / L;
[0111] The acetic acid solution is used for pickling for 5 hours in step 3;
[0112] The carbonization atmosphere in step 3 is argon, and the carbonization process is: heating from room temperature to 700°C at a heating rate of 2°C / min, and then carbonizing at 700°C for 2.0h;
[0113] After being taken out in step 3, the mixture is washed with water until the pH value reaches 7.0, which is neutral.
[0114] The alginate-based carbon aerogel-loaded cobalt-lead carbonate composite material prepared in Example 1, the lead carbonate-loaded sodium alginate carbon aerogel composite material prepared in Comparative Example 1, and the cobalt-doped sodium alginate carbon aerogel composite material prepared in Comparative Example 2 were tested for electrochemical properties of electrocatalysts in an H-type battery using an electrochemical workstation; 3 mg of the aerogel composite material was dispersed in 25 μL of Nafion (5 wt.%) solution, 125 μL of ethanol (C2H6O; 75%), and 125 μL of distilled water, and a uniform catalyst ink was obtained by ultrasonic dispersion; 300 μL of the ink was evenly drop-coated on a carbon sheet (1 cm×1 cm), using this catalyst-loaded carbon sheet electrode as the working electrode, a platinum sheet (1cm×1cm) as the counter electrode, and Ag / AgCl as the reference electrode. The Nafion117 membrane was inserted between the cathode chamber and the anode chamber of the H-type electrolytic cell, and the test was carried out in 0.1M KHCO3 electrolyte; before the measurement, the KHCO3 electrolyte was purged with N2 for 30 minutes, and then switched to carbon dioxide ventilation and sweeping until the electrolyte was saturated; during the electrochemical measurement, carbon dioxide was continuously introduced to ensure continuous carbon dioxide saturation during the test; the LSV curve was scanned from 0 to -1.2V at a scan rate of 10mV / s. vs.RHE (reversible hydrogen electrode (RHE): potential (V vs.RHE = applied potential (V vs.Ag / AgCl) + 0.197 + 0.0591 × pH); It curve is tested for 60 min between -0.6V vs.RHE and -1.2V vs.RHE; after electrolysis, the gas produced in the cathode chamber is directed to a gas chromatograph to identify and quantify the gaseous products, and 2 mL of the electrolyte product in the cathode chamber is collected using a needle syringe; high performance liquid chromatography is used for analysis at a wavelength of 210 nm, and the standard solution of formate is measured to obtain a calibration curve and then analyze and quantify the liquid product.
[0115] Figure 1 is a scanning electron microscope image of the alginate-based carbon aerogel-loaded cobalt-lead carbonate composite material prepared in Example 1;
[0116] from Figure 1 It can be seen that the alginate-based carbon aerogel-loaded cobalt-lead carbonate composite material prepared in Example 1 has a nanosheet structure and presents a porous morphology, providing more reactive sites for the reaction.
[0117] Figure 2 is a transmission electron micrograph of the alginate-based carbon aerogel-loaded cobalt-lead carbonate composite material prepared in Example 1;
[0118] from Figure 2 It can be seen that the particle size of the nanoparticles loaded on the nanosheets of the alginate-based carbon aerogel-loaded cobalt-lead carbonate composite material prepared in Example 1 is between 16 and 26 nm.
[0119] Figure 3 is a high-resolution transmission electron microscopy image of the alginate-based carbon aerogel-loaded cobalt-lead carbonate composite material prepared in Example 1;
[0120] from Figure 3 It can be seen that the lattice spacing of lead carbonate is captured in the lattice fringes of the alginate-based carbon aerogel-loaded cobalt-lead carbonate composite material prepared in Example 1, proving that the lead in the material exists in the form of lead carbonate.
[0121] Figure 4 It is a linear scanning curve of the alginate-based carbon aerogel-loaded cobalt-lead carbonate composite material prepared in Example 1 under CO2 saturation and N2 saturation conditions measured by an electrochemical workstation and an H-type electrolytic cell;
[0122] from Figure 4 It can be seen that compared with the current response under N2 saturated conditions, the current response of the alginate-based carbon aerogel-loaded cobalt-lead carbonate composite material prepared in Example 1 under CO2 saturated conditions is higher, proving that the material has the characteristics of carbon dioxide reduction.
[0123] Figure 5 is the Faraday efficiency of the product of the alginate-based carbon aerogel-supported cobalt-lead carbonate composite material prepared in Example 1 at a voltage of -0.6 V vs. RHE to -1.2 V vs. RHE, in which 1 is hydrogen, 2 is carbon monoxide, and 3 is formic acid;
[0124] from Figure 5 It can be seen that the alginate-based carbon aerogel-loaded cobalt-lead carbonate composite material prepared in Example 1 has excellent selectivity for the reduction of carbon dioxide to formic acid, and achieves a Faradaic efficiency of 98.15% for the production of formic acid under a voltage condition of -0.7 V vs. RHE. At the same time, the production of competing products H2 and CO under this voltage condition is negligible.
[0125] Figure 6 The stability of the catalyst of the alginate-based carbon aerogel-supported cobalt-lead carbonate composite material prepared in Example 1 at a voltage of -0.7 V vs. RHE for 12 h;
[0126] from Figure 6It can be seen that the alginate-based carbon aerogel-loaded cobalt-lead carbonate composite material prepared in Example 1 has excellent stability. After 20 hours of testing, the current density decayed by 13.47%, and the Faraday efficiency of formic acid production decayed by 3.86%.
[0127] Figure 7 It is a linear scanning curve of the lead carbonate-loaded sodium alginate carbon aerogel composite material prepared in Comparative Example 1 under CO2 saturation and N2 saturation conditions measured by an electrochemical workstation and an H-type electrolytic cell;
[0128] from Figure 7 It can be seen that compared with the current response under N2 saturated conditions, under CO2 saturated conditions, the current response of the lead carbonate loaded sodium alginate carbon aerogel composite material prepared in Comparative Example 1 is higher, proving that the material has the characteristics of carbon dioxide reduction.
[0129] Figure 8 It is the Faraday efficiency of the product of the lead carbonate-loaded sodium alginate carbon aerogel composite material prepared in Comparative Example 1 at a voltage of -0.6 V vs. RHE to -1.2 V vs. RHE, in which 1 is hydrogen, 2 is carbon monoxide, and 3 is formic acid;
[0130] from Figure 8 It can be seen that the lead carbonate-loaded sodium alginate carbon aerogel composite material prepared in Comparative Example 1 has relatively excellent selectivity for reducing carbon dioxide to formic acid, and achieves a Faradaic efficiency of 58.74% for producing formic acid under a voltage condition of -0.7 V vs. RHE. At the same time, the Faradaic efficiency of producing formic acid under all voltage conditions is higher than that of carbon monoxide and hydrogen.
[0131] Fig. 9 The stability of the catalyst of the lead carbonate-loaded sodium alginate carbon aerogel composite prepared in Comparative Example 1 at a voltage of -0.7 V vs. RHE for 10 h;
[0132] from Fig. 9 It can be seen that the lead carbonate-loaded sodium alginate carbon aerogel composite material prepared in Comparative Example 1 has a certain stability. After 10 hours of testing, the current density decayed by 54.05%, and the Faraday efficiency of formic acid production decayed by 4.8%.
[0133] Fig.10 It is a linear scanning curve of the carbon aerogel composite material of cobalt-doped sodium alginate prepared in Comparative Example 2 under CO2 saturation and N2 saturation conditions measured by an electrochemical workstation and an H-type electrolytic cell;
[0134] from Fig.10It can be seen that compared with the current response under N2 saturated conditions, under CO2 saturated conditions, the current response of the cobalt-doped sodium alginate carbon aerogel composite material prepared in Comparative Example 2 is higher, proving that the material has certain carbon dioxide reduction properties.
[0135] Fig.11 It is the Faraday efficiency of the product of the cobalt-doped sodium alginate carbon aerogel composite material prepared in Comparative Example 2 at a voltage of -0.6 V vs. RHE to -1.2 V vs. RHE, in which 1 is hydrogen, 2 is carbon monoxide, and 3 is formic acid;
[0136] from Fig.11 It can be seen that the cobalt-doped sodium alginate carbon aerogel composite material prepared in Comparative Example 2 achieved a Faraday efficiency of 41.16% formic acid production under a voltage condition of -1.2 V vs. RHE, and had a certain selectivity for reducing carbon dioxide to generate formic acid.
[0137] Fig.12 The stability of the catalyst of the cobalt-doped sodium alginate carbon aerogel composite material prepared in Comparative Example 2 at a voltage of -1.2 V vs. RHE for 10 h;
[0138] from Fig.12 It can be seen that the cobalt-doped sodium alginate carbon aerogel composite material prepared in Comparative Example 2 has a certain stability. After 10 hours of testing, the current density decayed by 52.38%, and the Faraday efficiency of formic acid production decayed by 4.62%.
Claims
1. A method for preparing a carbon aerogel-loaded cobalt-lead carbonate composite material based on alginate, characterized in that The preparation method is specifically completed according to the following steps:
1. Preparation of sodium alginate-based cobalt-lead hydrogel: ① Dissolve sodium alginate in deionized water and stir thoroughly to obtain sodium alginate hydrogel; ②、Configuration containing Co 2+ With Pb 2+ The salt solution is stirred evenly to obtain a cobalt-lead salt ion solution; ③, adding sodium alginate hydrogel dropwise into the cobalt-lead salt ion solution, stirring evenly, taking out after soaking for a certain period of time, washing, and obtaining sodium alginate-based cobalt-lead hydrogel; 2. Preparation of aerogel: The sodium alginate-based cobalt-lead hydrogel is frozen by liquid nitrogen and then placed in a freeze dryer for freeze drying to obtain the sodium alginate cobalt-lead aerogel; 3. Carbonization: The cobalt-lead aerogel of sodium alginate is placed in a tubular furnace for carbonization, then soaked and pickled with an acetic acid solution, taken out and washed with water to obtain a carbon aerogel composite material of cobalt-doped lead oxide loaded with sodium alginate; the carbon aerogel composite material of cobalt-doped lead oxide loaded with sodium alginate is immersed in a 0.1 mol / L KHCO3 electrolyte saturated with carbon dioxide to obtain a carbon aerogel-loaded cobalt-lead carbonate composite material based on alginate.
2. The method for preparing a carbon aerogel-loaded cobalt-lead carbonate composite material based on alginate according to claim 1, characterized in that The mass fraction of sodium alginate in the sodium alginate hydrogel described in step 1① is 1%; and the stirring in step 1① is sufficient to stir until there are no bubbles.
3. The method for preparing a carbon aerogel-loaded cobalt-lead carbonate composite material based on alginate according to claim 1, characterized in that The cobalt-lead salt ion solution in step 1② is 2+ The concentration of Pb is 0.1 mol / L. 2+ The concentration is 0.2mol / L.
4. The method for preparing a carbon aerogel-loaded cobalt-lead carbonate composite material based on alginate according to claim 1, characterized in that The soaking time described in step 1③ is 5h.
5. The method for preparing a carbon aerogel-loaded cobalt-lead carbonate composite material based on alginate according to claim 1, characterized in that The washing described in step 1③ is to use deionized water to wash until the filtered water is transparent and colorless.
6. The method for preparing a carbon aerogel-loaded cobalt-lead carbonate composite material based on alginate according to claim 1, characterized in that The freeze-drying temperature in step 2 is -80°C, and the freeze-drying time is 24 hours.
7. The method for preparing a carbon aerogel-loaded cobalt-lead carbonate composite material based on alginate according to claim 1, characterized in that The concentration of the acetic acid solution described in step three is 1 mol / L; the immersion pickling time using the acetic acid solution in step three is 5 hours.
8. The method for preparing a carbon aerogel-loaded cobalt-lead carbonate composite material based on alginate according to claim 1, characterized in that The carbonization atmosphere in step 3 is argon, and the carbonization process is: heating from room temperature to 700° C. at a heating rate of 2° C. / min, and then carbonizing at 700° C. for 2.0 h.
9. The method for preparing a carbon aerogel-loaded cobalt-lead carbonate composite material based on alginate according to claim 1, characterized in that After being taken out in step 3, the mixture is washed with water until pH = 7.0, which is neutral; in step 3, the carbon aerogel composite material doped with lead oxide and loaded with sodium alginate is immersed in a 0.1 mol / L KHCO3 electrolyte saturated with carbon dioxide for 0.5 h.
10. Use of a carbon aerogel-loaded cobalt-lead carbonate composite material based on alginate prepared by the preparation method according to claim 1, characterized in that An alginate-based carbon aerogel-supported cobalt-lead carbonate composite was used as a CO2RR catalyst.